Modeling the Dispersal of Spiny Lobster (Palinurus elephas) Larvae: Implications for Future Fisheries Management and Conservation Measures - Whomersley, Paul; Van der Molen, Johan; Holt, Douglas; Trundle, Colin; Clark, Sarah; Fletcher, David (Frontiers in Marine Science, 2018)
Knowledge of larval dispersal, population dynamics and connectivity in relation to the management and conservation of commercially important species is vital if existing fisheries are to remain sustainable into the future. Larval dispersal of the commercially exploited spiny lobster, Palinurus elephas, was modelled from Marine Protected Areas located in the southwest of England for a 16-month period using a General Individuals Transport Model (GITM). The model included physical particle advection based on current fields from a 3D hydrodynamics model and a larval behaviour module. Our results demonstrate the overall dispersal patterns of P. elephas larvae and highlight populations capable of self-seeding and those which are seemingly reliant on larvae from more distant populations. The results indicate where further research may be required to fully understand how populations of P. elephas are maintained at regional, national and international scales while providing us with the opportunity to discuss the effectiveness of current approaches to conservation and fisheries management.